ANALISIS PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014) - Abdullah Rahman, Elizabeth Vita (Jurnal Ekonomi Perusahaan, 2017)
Firm’s value became one of the orientation of the company other than the maximization of profit. High firm’s value will make the market believe t hat the performance and prospects of the company in the future is very good. Maximizing firm’s value is very important for the company, because it can maximize shareholder wealth reflected in the company's stock price. Price to Book Value (PBV) measures the value given to the management of financial markets and corporate organizations as the company continues to grow. Price to Book Value Ratio is the ratio between the market value of the shares according to the book value of the equity of the company. The book value is calculated as the quotient between shareholders with the number of shares outstanding. Therefore, the higher the value of PBV, the firm's value will be higher. This research was conducted to examine the effect of several variables expected to influence firm’s value, namely: capital structure, dividend policy, and firm size. The object of this research is manufacturing companies that have been listed in the Indonesia Stock Exchange (BEI) from 2012-2014. Sampling technique used is purposive sampling. The data were analyzed with Overall Fit valuation, descriptive analysis, f-test, t-test, and R² test. The results of this research showed that in the period 2012-2014, capital structure variable and dividend policy variable have a positive and significant influence on Firm’s Value. Meanwhile, firm size variable have no effect on Firm’s Value. Keywords: Capital Structure, Dividend Policy, Firm Size, Firm’s Value, Price to Book Value.